Changes in the utilization of prenatal and delivery services in the United States prior to, during, and after the COVID-19 pandemic - Hannah Silverstein; Larissa Jennings Mayo-Wilson; Anna Austin (Reproductive Health)
Abstract Background Starting in March 2020, the COVID-19 pandemic strained the healthcare system in the United States, directly and indirectly changing the provision of many types of care, including maternity care. This paper describes longer-term changes in maternal health services utilization in the U.S. during the COVID-19 pandemic. Methods Using United States monthly aggregated birth record data from 2016 to 2023, we examined changes in the average number of prenatal visits (overall and by delivery pay type) and total births (overall, by pay type, and by birthplace) before, during, and after the pandemic. We estimated monthly time series models replicating pre-pandemic patterns from January 2016 to February 2020. We then extended those models to predict monthly levels of each outcome had COVID-19 not occurred from March 2020 through December 2023. We compared observed and predicted levels from March 2020 onward, assessing differences associated with COVID-19. Results There were persistent and significantly lower-than-expected levels of average number of prenatal care visit across all COVID-19 months. There was also a temporary significant drop in total births during 2020 that recovered to expected levels in 2021, except for an increase in the total self-pay births in 2023. Patterns by pay type were similar to the overall patterns observed. Total non-hospital births were significantly higher than expected for the entirety of the pandemic, with large increases in intentional home births. Conclusion Most initial changes to maternity care persisted throughout and continued after the pandemic, resulting in lower levels of prenatal care visits and higher numbers of home births. These findings show sustained changes to maternity care provision and access prompted by COVID-19, which highlight how vulnerable maternity services are to healthcare disruptions and suggest prolonged effects on equitable access to safe care.